PREFERENCE FOR THE LANGUAGE OF THE LOCALS IN NAGARI UJUNG GADING, LEMBAH MELINTANG DISTRIC, PASAMAN BARAT - Midiawati Midiawati; Rina Marnita; Reniwati Reniwati (Politeknik Negeri Padang, 2023)
This article describes types of language choices by speakers of different ethnic and linguistic backgroundsinUjung Gading, a nagari in Pasaman, West Sumatera, Indonesia, where speakers of the Mandailing, Minangkabau, andJavanese languages have lived for a long time in harmony. Data for this descriptive qualitative study was obtainedfromdirect observation of the use of language by selected speakers in family and public domains in the region. The datawererecorded, and interviews were done to gain information on the socio-cultural and linguistic backgrounds of thespeakers.Fishman’s (1972) domain is used for language choice analysis. Ninety speech events with a different type of languagechoice are observed. Intra-language switching is the most dominant type (67%), indicating that communicationinfamilydomains is still conducted in everybody’s native language. Code-mixing and code-switching are mostly encounteredincommunication between the speakers of the Mandailing and Minangkabau languages, showing that bothpartieshaveaknowledge of each other’s language and an ability, with a different degree, to switch to the language of the interlocutors.Javanese speakers do not have this ability and use Indonesian instead of conversing with a speaker of otherlocallanguages. Unlike in most bilingual or multilingual societies in Indonesia, here the Indonesian language is notthelanguage of instruction in the public domain. Thus, it is not a threat to the existence of the local language.